A gestão escolar no Colégio Tiradentes da Polícia Militar de Minas Gerais - Leandro Estevão Moreira Santos (2024)
This research is inserted in the field of studies about school management, and it aims to understand how this management happens in Colégio Tiradentes da Polícia Militar de Minas Gerais (CTPM). In the follow-up of that goal, the study here presented has as its motto the military and non-military subjects that are part of the managing team of CTPM. In this sense, the research sought to characterize this management, considering the different models that have been constituted in the country, among them the model that dialogs with the idea of hybridization. This perspective of a hybrid is seen from two different main approaches, which are the participation of military personnel in public education and the modifications implemented post management reform in the Brazilian State in the 90s. In our theoretical and analytical framework, we address the field of management and administration of school systems, militarism and the emergence of new management models and the influence of New Public Management. The methodological path of the research, aiming to characterize and understand the emergence of this school management, was carried out through content analysis. Coming from an initial phase of documental research and constitution of the research’s corpus we’ve used the content analysis on the documents that rule and verse on school management of CTPM. The results obtained in this analytical process point out to the existence of a technical division of labor which is established from the socio-professional links of the manager, considering the condition of being a military or non-military the main factor of this division. Furthermore, it is noticeable that the dualism (military and non-military) present in the composition of managements seats in a normative dissention from the legislation that regulates school management in Brazil and in Minas Gerais before the norms practiced in Colégio Tiradentes, with conversions and diversions between them both. Lastly, the adoption of managerial practices, originated in New Public Management in this schooling network is concluded.